Soil microbial ecology in brazilian restingas: Influence of phytophysiognomies and edaphic attributes (Research, Society and Development, 2026)
Brazilian restingas constitute coastal ecosystems marked by high phytophysiognomic heterogeneity and strong edaphic restrictions—conditions that directly influence the composition, diversity, and functioning of soil microbial communities. In this context, the present study aimed to gather, organize, and analyze scientific evidence on soil microbial ecology in Brazilian restingas, highlighting the influence of phytophysiognomies and edaphic attributes on the microbiota. The gathered evidence indicates that the phytophysiognomic heterogeneity of restingas, associated with gradients of drainage, salinity, fertility, organic matter, and water regime, acts as an important organizing axis for the soil microbiota. The results also show that the restinga presents a distinct microbial composition compared to adjacent ecosystems, such as mangroves and Atlantic Forest, in addition to harboring relevant symbiotic groups, especially mycorrhizal fungi, which remain insufficiently explored. It is concluded that the microbial ecology of restingas must be interpreted through an integrated approach between soil, vegetation, and microorganisms, an understanding that is fundamental for advancing ecological knowledge and supporting conservation strategies for fragile and threatened coastal environments.